2023
DOI: 10.1177/09603271221141695
|View full text |Cite
|
Sign up to set email alerts
|

MiR-155-5p-SOCS1/JAK1/STAT1 participates in hepatic lymphangiogenesis in liver fibrosis and cirrhosis by regulating M1 macrophage polarization

Abstract: Background The role and underlying mechanism of liver macrophages and their derived miR-155-5p in hepatic lymphangiogenesis in liver fibrosis remain unclear. Here, we investigated the mechanism by which macrophages and miR-155-5p were involved in lymphangiogenesis during liver fibrosis and cirrhosis. Methods In vivo, hepatic lymphatic vessel expansion was evaluated; the liver macrophage subsets, proportion of peripherally-derived macrophages and expressions of CCL25, MCP-1, VAP-1 and MAdCAM-1 were documented; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…STAT1 and STAT6 are also involved in regulating macrophage polarization. Specifically, the STAT1 pathway facilitates macrophage polarization to the M1 phenotype [ [229] , [230] , [231] , [232] , [233] ], whereas the STAT6 pathway promotes macrophage polarization to the M2 phenotype [ [234] , [235] , [236] ]. Upregulation of STAT6 expression in TAMs leads to their polarization to the M2 phenotype and plays a role in regulating tumor angiogenesis [ 237 ].…”
Section: Modulation Of Tams By Nanomaterials For Hcc Treatmentmentioning
confidence: 99%
“…STAT1 and STAT6 are also involved in regulating macrophage polarization. Specifically, the STAT1 pathway facilitates macrophage polarization to the M1 phenotype [ [229] , [230] , [231] , [232] , [233] ], whereas the STAT6 pathway promotes macrophage polarization to the M2 phenotype [ [234] , [235] , [236] ]. Upregulation of STAT6 expression in TAMs leads to their polarization to the M2 phenotype and plays a role in regulating tumor angiogenesis [ 237 ].…”
Section: Modulation Of Tams By Nanomaterials For Hcc Treatmentmentioning
confidence: 99%
“…This finding provides new insights into the development of novel therapeutic strategies for combatting HBV + HCC and a new reference for exploring antitumor immunotherapy ( 61 ). Recently, it has been reported that miR-155-5p can regulate M1-type macrophage polarization by targeting downstream SOCS1/JAK1/STAT1 axis and participate in liver fibrosis and hepatic lymphangiogenesis in cirrhosis ( 62 ). Besides, miR-155-5p can regulate M1 polarization by other pathways, such as SOCS1/NF-κB pathway ( 63 ), and let-7a-5p can also target suppressor of cytokine signaling 1 (SOCS1) to modulate NF-κB, and activate M1 macrophages ( 64 ).…”
Section: The Role Of Mirnas In Macrophage Polarizationmentioning
confidence: 99%